Combined high-intensity interval and resistance training improves cardiorespiratory fitness more than high-intensity interval training in young women with overweight/obesity: a randomized controlled trial - Wang, Yifei; Yang, Xin; Deng, Jiamei; Wang, Zhenshan; Yang, Dongxue; Han, Yanbai; Wang, Hongli (Frontiers in Endocrinology, 2024)
Objective This study aimed to compare the effects of high-intensity interval training (HIIT) combined with resistance training (RT) versus HIIT alone on body composition, cardiorespiratory fitness and glycolipid metabolism in young women with overweight/obesity. Methods This randomized controlled trial divided 40 subjects into an experimental group (HIIT+RT) and a control group (HIIT). Both groups underwent training three times per week for eight weeks. Body composition, cardiorespiratory fitness and glycolipid levels were assessed before and after the intervention. Results The results revealed that compared to baseline, both the experimental and control groups showed significant improvements in body weight, body mass index (BMI), Body fat, waist circumference (WC), waist-hip ratio (WHR), peak oxygen uptake (VO2peak), vital capacity (VC), oxygen pulse (VO2/HR), minute ventilation, resting heart rate, blood oxygen saturation, blood pressure, fasting blood glucose, triglycerides and high-density lipoprotein cholesterol (p<0.05). Additionally, a significant increase in muscle mass and a significant reduction in 2-hour postprandial glucose were observed in the experimental group (p<0.05). Muscle mass (mean difference: 2.75%), VO2peak (mean difference: 1.61 mL/min/kg), VC (mean difference: 334mL), and VO2/HR (mean difference: 0.51mL/beat) showed greater improvement in the HIIT+RT group compared to the HIIT group (p<0.05). Conclusion In conclusion, an 8-week regimen of either combined HIIT and RT or HIIT significantly improves body composition, cardiorespiratory fitness and glycolipid metabolism in women with overweight/obesity. However, the combined training appears to offer more benefits than HIIT alone. Further research is needed to evaluate the long-term effects and feasibility of combined training. Trial registration https://www.chictr.org.cn/, identifier ChiCTR2300075961.